Utilization of Jack Bean (Canavalia ensiformis) Meal as a Substitute for Soybean Meal in Diet for Broiler Reared for 35 Days - Asep Sudarman; Anggun Marsiz Jayanti; Rita Mutia (Faculty of Animal Science, Universitas Gadjah Mada, 2018)
This study was aimed to evaluate the utilization of jack bean meal as a substitution of soybean meal in the diets and the effect on broiler performance. A total number of two hundred Lohmann MB 202 Platinum broiler chickens were kept in five weeks rearing period, consisted of three weeks of starter phase (0-3 weeks) and two weeks of finisher phase (3-5 weeks). This study used a completely randomized design with four treatments and five replicates. The dietary treatments were: JB0-0 (control ration: basal diet without jack bean meal substitution in starter and in finisher phase), JB50-0 (basal diet with jack bean meal substitution in starter phase only), JB50-50 (basal diet with jack bean meal substitution in starter and in finisher phase), JB0-50 (basal diet with jack bean meal substitution in the finisher phase only). The data obtained were statistically analyzed using analysis of variance and followed with Duncan's multiple-range test for the data with significant difference. The variables measured were: growth performance, carcase yield, visceral organ weight and immune organ. Results showed that the dietary treatment had no effect on performance, carcass yield and commercial cut, visceral organ or immune organs of 35 days old broiler chickens, except for the thymus (P<0.05). It can be concluded that as a source of protein, soybean meal can be replaced by jack bean meal up to 50%. Jack bean meal can be given either in starter phase only, in finisher phase only, or in both starter and in finisher phase.